Research Misconduct as White-Collar Crime A Criminological Approach - Faria, Rita (Springer International Publishing, 2018)
This book explores the subject of research misconduct: its definition, what behaviours should fall under its label, and the types of preventive and repressive procedures that should be put to practice to combat it. Adopting a criminological perspective, Faria views research misconduct as a locus of analysis for corporate and white-collar crime. Based upon an empirical study involving in-depth interviews and documentary analysis, this original research offers an interesting approach to an age-old problem which is growing ever more important. The commodification of research - together with perceived risks of research misconduct - is opening the way to ambiguous and ineffective forms of social control over scholars, affecting their commitment to research integrity and the responsible conduct of research. Despite this, however, little consensus around the phenomenon exists. Seeking to counter this, Faria opens up the discussion on the potential social harms arising from the current state of affairs, and argues that that criminology should task itself with understanding and researching the pressing topic of research misconduct, including fabrication, falsification, and plagiarism, as well as questionable research practices. .